서해안으로 내습하는 폭풍해일 예측모형의 정밀도 개선, Development of a near real-time forecasting system for storm surge and coastal inundation - Jong-Joo Yoon, Jae-Seol Shim (충남연구원, 2016)
Climate change is resulting in an increase in disastrous effects, such as sea level rise, intensity and frequency of storms, abnormal waves, and storm surges, in densely populated coastal areas. In particular, the coast of Korea was repeatedly damaged by storm surge and subsequent inundation caused by the approach of strong typhoons. Therefore, it is desirable to accurately forecast storm surge height and coastal inundation. In this study, a rapid, near real-time forecasting system was developed for addressing coastal inundation. A primary study of this system for operational forecasting using typhoon advisories was conducted and applied for the 2012 typhoon Sanba. To develop this forecasting system, a systematic investigation of storm surge impacts to the Korean coast was conducted using the unstructured grid model, FVCOM. This model was employed to simulate near-future storm surges and their corresponding inundation characteristics. Observed surges and inland inundation data were used to validate the model with satisfactory results. In this forecasting system, full automatic computations according to typhoon advisories were conducted for each typhoon invasion and uploaded to the disaster warning system. Less than one hour from starting the calculation, all pre- and post-processing was completed using parallel clusters. We also collected field measurements to compare with simulated inundation results for typhoon Sanba. The forecasting simulation results agreed with the observational data. The system developed in this study could be useful as a pre-warning system to prompt preparation of detailed evacuation plans that address storm surge inundation problems.
Keywords: Storm surge; Operational prediction system; TC96; FVCOM; Numerical simulation